A prospective observational study to compare efficacy of topical triamcinolone acetonide 0.1% oral paste, oral methotrexate, and a combination of topical triamcinolone acetonide 0.1% and oral methotrexate in moderate to severe oral lichen planus. Issue 1 (10th November 2017) - Chauhan, P.; De, D.; Handa, S.; Narang, T.; Saikia, U. N.
Abstract: Topical corticosteroids are considered to be the most effective treatment for oral lichen planus (OLP). Methotrexate has been found to be effective in extensive cutaneous lichen planus. The objectives of the study were to evaluate the clinical efficacy and safety of topical triamcinolone 0.1% oral paste, oral methotrexate and a combination of these in symptomatic moderate‐to‐ severe OLP. Forty‐five patients were recruited and were allocated to three treatment arms with 15 patients in each treatment arm. They were treated for a period of 16 weeks or until complete clinical remission, whichever was earlier. The parameters assessed were clinical severity score, visual analogue score, and quality of life impairment questionnaire score. Forty‐three patients completed the study. All three treatment modalities were effective. The patients in the combination group had significantly better reduction in the outcome parameters assessed compared to the other two groups. Nine patients achieved complete clinical remission, 6 in the combination group and 3 in the topical triamcinolone group. Systemic methotrexate, alone or in combination with topical triamcinolone, is effective in management of moderate to severe OLP.